Three semi-synthetic approaches to a set of curdlan sulfate polysaccharides with different sulfation patterns - Esposito, Fabiana; Zabłocka, Agnieszka; Traboni, Serena; Iadonisi, Alfonso; Górska, Sabina; Bedini, Emiliano (Frontiers in Molecular Biosciences, 2025)
IntroductionCurdlan is a linear homopolysaccharide composed of β-1→3-linked glucose units. It is extracted from some bacteria as an exopolysaccharide and employed in the food industry due to its remarkable rheological and thermal behaviors. Furthermore, its ability to form gel encapsulations with several drugs and its roles in innate and adaptive immunity have fueled an increasing interest in pharmaceutical applications of curdlan and its derivatives. Among them, curdlan sulfate derivatives disclosed not only a highly enhanced water solubility concerning native curdlan but also an efficient immunomodulatory potential in both in vitro and in vivo assays.MethodsTo detect the effects of the sulfation degree and sulfation pattern on the immunological activity of curdlan sulfate, a set of regioselectively sulfated curdlan polysaccharides was semi-synthesized and fully characterized utilizing nuclear magnetic resonance (NMR) spectroscopy techniques.ResultsAlthough some regioselectively sulfated curdlan derivatives were already reported some years ago, in this work, a comprehensive semi-synthetic study was developed by investigating three different, complementary approaches based on direct regioselective sulfation or desulfation reactions or multistep protection–sulfation–deprotection procedures.DiscussionSome of the semi-synthesized curdlan sulfate derivatives were selected as representatives of different sulfation degrees and patterns and subjected to a panel of immunological assays to define some structure–activity relationships.